FINANCIAL DECISION‑MAKING PRACTICES AND BUSINESS GROWTH OF SMALL AND MEDIUM ENTERPRISES IN NORTH‑WEST NIGERIA: AN EMPIRICAL VALIDATION - Abdulsalam Dauda; Bamidele Vincent Olawale (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study empirically examines how financial decision‑making (FDM) practices influence the business growth of small and medium enterprises (SMEs) operating within Nigeria’s North‑West geopolitical zone. In an environment characterized by financial exclusion, insecure markets, and information asymmetry, sound decision processes regarding investment, financing, and working‑capital management are vital for long‑term survival. Drawing on Agency Theory and the Pecking Order Theory, the study employed a quantitative correlational design based on primary data collected from 332 SME owners and managers across Jigawa, Kaduna, Kano, Katsina, Kebbi, Sokoto, and Zamfara States. Data were analyzed using Ordinary Least Squares (OLS) and Generalized Linear Model (GLM) techniques. Results indicate that financial decision‑making exerts a positive and statistically significant effect on business growth (β = 1.563; p < 0.001). Firms that systematically appraise investments, manage debt‑equity structure prudently, and maintain disciplined working‑capital control record higher sales and asset growth, contributing directly to regional employment. The model explains 67.4% of observed growth variation (Adjusted R² = 0.674) and passes robustness validation under a gamma‑distributed GLM specification (Deviance/df = 1.03). The study concludes that effective financial decision‑making is a cornerstone of SME expansion. It recommends capacity‑building on investment evaluation, debt management, and liquidity optimization, emphasizing that institutional partnerships between SMEDAN, microfinance banks, and training institutions can strengthen this capability. The research contributes region‑specific evidence to SME‑finance literature and demonstrates the continuing relevance of rational financial decision frameworks in resource‑constrained contexts.